Online survey for symptoms following COVID-19 postvaccination in Karnataka: A cross-sectional study - V A Kotiwale; A B Kudachi; S K Rajashree; V V Kotiwale (Wolters Kluwer Medknow Publications, 2022)
Background: While the protective efficacy of vaccine is frequently discussed, little is known about the real-world postvaccination experience outside of clinical trial conditions. The objective of the study was to assess the immediate response to the first and second dose of COVID-19 vaccine and to study the spectrum of postvaccination symptom profile for individuals' vaccines. Materials and Methods: A cross-sectional online survey was done using Google Forms. It was circulated via electronic media to the people who had taken COVID-19 vaccine from July 1 to July 30, 2021. Data were analyzed using SPSS version 20.00. Results: A total of 610 people responded to the online survey. Majority (29%) of respondents belonged to the 20-30 years' age group, followed by 30-40 years' age group (24%). The respondents were predominantly males (82%) and belonging to urban area (57%). Almost 57% of the people had taken Covishield, with the rest having received Covaxin. About 53% of the people had taken the first dose of vaccine. The respondents reported postvaccination symptoms as follows: fever (56%), muscle pain (47%), headache (45%), redness (35%), tiredness (33%), itching (30%), joint pain (30%), and swelling (27%). A total of 45% of participants experienced some health problems and 69% had taken medications after vaccination to relieve the symptoms. A statistically significant association was observed between first dose of COVID-19 vaccine and gender of the participants (P = 0.0024). A similar association was also observed between the dose of COVID-19 vaccine and presence of postvaccination symptoms, namely, fever (P = 0.0001), headache (P = 0.0001), muscle pain (P = 0.0010), tiredness (P = 0.029), breathlessness (P = 0.001), and joint pains (P = 0.012). Conclusion: Post-COVID vaccination symptoms are very common in the community irrespective of age and gender.